Hydrate Precursor Test Method for the Laboratory Evaluation of Kinetic Hydrate Inhibitors - Duchateau, Christophe; Glénat, Philippe; Pou, Tong-Eak; Hidalgo, Manuel; Dicharry, Christophe (Energy & fuels, 2010)
Because of the stochastic character of hydrate crystallization, the evaluation of kinetic hydrate inhibitor (KHI) performance, using high-pressure autoclaves, is subject to the substantial dispersion of experimental results. To overcome this problem, we proposed in a previous paper (Duchateau et al. Energy Fuels 2009, 23 (2), 962−966) a testing procedure based on “water memory”. The residual structures remaining in solution after a prior hydrate formation/dissociation cycle act as hydrate precursors in the subsequent formation, which yields less-scattered results. The present work shows that the comparison between the subcoolings ΔT sub,lim (difference between the hydrate equilibrium temperature and the crystallization temperature at hydrate reformation when a constant cooling rate is applied), measured with and without an additive at hydrate reformation is a convenient way to evaluate the potential of the additive to inhibit hydrate growth. It would also appear to be possible to rank the KHIs when the values of ΔT sub,lim are compared. On the other hand, the comparison of the KHI effectiveness in terms of hold time (difference between the onset of catastrophic hydrate growth and the time at which the test solution enters the hydrate stability domain) at subcoolings lower than ΔT sub,lim using the precursor test method should be made with caution.